2004
DOI: 10.1002/ppul.10434
|View full text |Cite
|
Sign up to set email alerts
|

Is clinical wheezing reliable as the endpoint for bronchial challenges in preschool children?

Abstract: The present study was designed to compare the clinical finding of wheeze by auscultation with an objective evaluation by acoustic means at the endpoint of a bronchial challenge in preschool children. Challenges were undertaken using a tidal breathing method in 51 preschool children as part of the investigation of possible asthma. An electronic stethoscope was used for auscultation of each lung and for the simultaneous recording of the acoustic sonogram for analysis. In 24 children, the pediatrician determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 13 publications
0
17
1
Order By: Relevance
“…Airway responsiveness to AMP has been shown to be more specific for asthma diagnosis both in preschool-age (21) and school-age children (22). It has even been used in some clinics as the bronchial challenge of choice in young children who were referred for a possible diagnosis of asthma with a chief complaint of unexplained cough without wheezing (23,24). In contrast to its popularity, there is very limited data about the rate of AHR to AMP in childhood asthma (21,22,25).…”
Section: Discussionmentioning
confidence: 99%
“…Airway responsiveness to AMP has been shown to be more specific for asthma diagnosis both in preschool-age (21) and school-age children (22). It has even been used in some clinics as the bronchial challenge of choice in young children who were referred for a possible diagnosis of asthma with a chief complaint of unexplained cough without wheezing (23,24). In contrast to its popularity, there is very limited data about the rate of AHR to AMP in childhood asthma (21,22,25).…”
Section: Discussionmentioning
confidence: 99%
“…77 Nevertheless, subjective assessment by physicians seems to compare favourably with computerized acoustic analysis, detecting wheeze with very high sensitivity, and specificity as long as the proportional wheeze time Tw/Ttot is at least 10%. 83 The low sensitivity of wheezing as an indicator of significant airway obstruction during bronchial provocation had been recognized in adults even before PCwheeze gathered interest. 84 It appears that a greater drop in FEV1, that is, more than 35% from baseline, is often required to elicit wheeze in children, 85 and adults.…”
Section: Relevancementioning
confidence: 99%
“…During subsequent years, this parameter was used in several studies of children, and adults, but the attraction of PCwheeze as an indicator of airway hyperreactivity has lessened somewhat since some studies showed sensitivity as low as 16% and specificity of only 43% . Nevertheless, subjective assessment by physicians seems to compare favourably with computerized acoustic analysis, detecting wheeze with very high sensitivity, and specificity as long as the proportional wheeze time Tw/Ttot is at least 10% …”
Section: Introductionmentioning
confidence: 99%
“…However, if spirometry is not performed, the safety of a patient must be ensured by other means, e.g. by pulseoximetry or by chest auscultation (19–22).…”
Section: Discussionmentioning
confidence: 99%